(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
This article explores the integration of cultural content into language lessons and its impact on learners’ communicative and intercultural competence. Using a mixed-methods approach involving proficiency tests, observations, and learner reflections, the study evaluates how cultural materials—such as authentic media and intercultural tasks—shape linguistic and affective outcomes. Findings reveal notable improvements in pragmatic competence, increased learner motivation, and stronger engagement with the target culture. Challenges related to interpreting unfamiliar cultural norms highlight the need for scaffolding and thoughtful material selection. The article concludes that cultural integration is essential for effective language teaching and should be implemented systematically and reflectively.